Effect of ginger (Zingiber officinale) on inflammatory markers: A systematic review and meta-analysis of randomized controlled trials. (November 2020) - Morvaridzadeh, Mojgan; Fazelian, Siavash; Agah, Shahram; Khazdouz, Maryam; Rahimlou, Mehran; Agh, Fahimeh; Potter, Eric; Heshmati, Shilan; Heshmati, Javad
Graphical abstract: Highlights: Ginger have anti-inflammatory cytokines properties. Ginger intake significantly decrease CRP, TNF-α serum levels, but not IL-6. Ginger efficiently act as an anti-inflammatory herbal complementary adjunct therapy. Abstract: The aim of this systematic review and meta -analysis was to investigate the efficacy of ginger supplementation on circulating levels of C-reactive protein (CRP), high sensitivity C-reactive protein (hs-CRP), tumor necrosis factor-alpha (TNF-α), soluble intercellular adhesion molecule (sICAM), and interleukin-6 (IL-6) concentrations in randomized controlled trials (RCTs). The search included PubMed-Medline, EMBASE, Scopus, Web of Science and Cochrane Library databases to identify randomized clinical trials on the effect of ginger supplementation on circulation levels of CRP, hs-CRP, IL-6, sICAM, and TNF-α published up until February 1st, 2020. We did not restrict articles based on language of publication. Standard mean differences and 95% confidence intervals were calculated for net changes in inflammatory mediators using a random-effects model. Sixteen RCTs comprising 1010 participants were found to be eligible for this meta -analysis. There was a significant reduction of circulating CRP (SMD: −5.11, 95% CI: −7.91, −2.30, I 2 = 98.1%), hs-CRP (SMD: −0.88, 95% CI: −1.63, −0.12, I 2 = 90.8%) and TNF-α levels (SMD: −0.85, 95% CI: −1.48, −0.21, I 2 = 89.4%) following ginger supplementation. However, meta -analysis results did not show any significant impact of ginger supplementation on IL-6 (SMD: −0.45, 95% CI: −1.29, 0.38, I 2 = 89.2%), and sICAM levels (SMD: −0.05, 95% CI: −0.36, 0.26, I 2 = 00.0%). This systematic review and meta -analysis of RCTs demonstrates a significant impact of ginger in lowering circulating CRP, hs-CRP and TNF-α levels. Large-scale RCTs are still needed to draw concrete conclusions about the effect of ginger on other inflammatory mediators.